Beginner-Aquarist - Kolosok, А. M.; Budnik, S. V. (My University, 2021)
The textbook contains the theoretical foundations of aquarium keeping as a hobby, creative tasks and self-check tests, guidelines and samples of educational activities on aquarium topics, photo materials of aquariums. The publication is developed in accordance with the curricula for bachelor's degree training “Primary education”, “Economics of Environment and Natural Resources”. This book can be used to study the following subjects such as “Basic Environmental Studies”, “Ecoculture of Personality”, “Ecological and naturalistic activities in primary school”, “Teaching methods in educational field of expertise”, “Environmental Studies”, “Extra-curricular and out-ofschool educational teaching internship, “Environmental Economics and Management”.For students of pedagogical specialties, teachers and educators in educational institutions.
Recommended for publication by Methodological Board of the Teachers’ Training College at Easteuropean National University named after Lesya Ukrainka (record № 2 від 25.02.2016.;order № 49-z від 29.02.2016; order № –45z from 22.02.2018; Teachers’ Training College record № 2 від 21.10.2021)
Keywords: aquarist; aquarium; 37.016: 597.2 /.5 (075.8)